Factors That Influence Exclusive Breastfeeding - Nurmaliza -; Yusmaharani; Desmariyenti; Nariyati (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Exclusive breastfeeding is the provision of breast milk without additional fluids, such as formula milk, honey, tea, water, or solid food. Exclusive breastfeeding until the baby is 6 months old has enormous benefits for the growth and development of the baby, only 42% of countries in the world have achieved exclusive breastfeeding coverage, while the global target is 75% by 2025. The impact of low exclusive breastfeeding in babies 0-6 months is that it can worsen diseases such as ISPA 35.09%, diarrhea 38.07%, and malnutrition 49.2%. The purpose of this study was to determine the factors that influence exclusive breastfeeding in the Payung Sekaki Community Health Center Working Area of ​​Pekanbaru City. This research method uses a quantitative analytical correlation design with a cross-sectional approach. The sample consisted of 40 mothers who breastfed babies 0-6 months who were selected using the Accidental Sampling technique. Data were collected through questionnaires and analyzed using the Chi-Square test with a significance level of 95%. The results of the study showed that there was a significant relationship between maternal knowledge and exclusive breastfeeding (P = 0.021). The results of statistical tests showed that there was a significant relationship between maternal attitudes and exclusive breastfeeding (P = 0.018). The results of statistical tests showed that there was a significant relationship between husband's support and exclusive breastfeeding (P = 0.004). Conclusion: There is a relationship between maternal knowledge, maternal attitudes, husband's support and exclusive breastfeeding.